Pengaruh Harga Emas, Harga Minyak, Kurs Tengah Bank Indonesia, dan Suku Bunga Acuan Bank Indonesia Terhadap Indeks Harga Saham Gabungan (IHSG) di Bursa Efek Indonesia Pada Periode Juli 2020 - Desember 2020 - marselia purnama purnama; Vivin Hanitha; Octavianti Purnama (Komunitas Dosen Indonesia, 2021)
This research was conducted on the price of the Composite Stock Price Index in the Indonesia Stock Exchange. In this study using purposive sample method as a sampling method. The samples used were gold prices, oil prices, Bank Indonesia middle rates, Bank Indonesia interest rates and IHSG from July 2020 to December 2020 so that 121 observational data were obtained. In testing the hypothesis in this study, it was carried out in five ways, namely the classical assumption test, multiple linear regression analysis, partial test (t test), simultaneous test (f test), and the coefficient of determination test. From the results of the eviews test, it is found that the gold price, Bank Indonesia middle rate, and Bank Indonesia interest rate partially have a significant effect on the JCI during the study period, while the world oil price partially does not have a significant effect on the JCI during the study period. Simultaneously the gold price, oil price, Bank Indonesia middle rate, and Bank Indonesia interest rate had a significant influence on the JCI during the study period with an adjusted R2 figure of 0.672175 or 67.22%, while the remaining 32.78% was influenced by variables. others who were not examined in this study.